Distinct Relationship Between Cognitive Flexibility and White Matter Integrity in Individuals at Risk of Parkinson’s Disease - Alzaid, Haidar; Ethofer, Thomas; Hobert, Markus A.; Kardatzki, Bernd; Erb, Michael; Maetzler, Walter; Berg, Daniela (Frontiers in Aging Neuroscience, 2020)
Background and objective: Executive dysfunction is the most common cognitive impairment in Parkinson’s disease (PD), occurring even in its early stages. In our study, we applied diffusion tensor imaging (DTI) to investigate white matter integrity and its association with a specific executive function such as cognitive flexibility in individuals with risk factors for PD. Methods: We examined 50 individuals with risk factors for developing Parkinson’s disease and 24 healthy controls from the TREND (Tübinger Evaluation of Risk Factors for Early Detection of Neurodegeneration) study including neuropsychological evaluation and DTI. Cognitive flexibility was assessed using the trail making test (TMT). Tract based spatial statistics (TBSS) were employed to assess white matter abnormalities and their correlation with cognitive flexibility. Results: TMT performance correlated with mean and axial diffusivity in several white matter regions, predominantly in the frontoparietal white matter. These effects were stronger in PD-RP than in controls as evidenced by a significant group interaction. White matter integrity and TMT performance did not significantly differ across groups. Conclusion: Based on our results, PD-RP do no exhibit white matter changes or impaired cognitive flexibility. However, specific executive functions in PD-RP are more related to white matter alterations than in healthy older adults.